Invited Editorial: Responding to Incivility in the Classroom: A Case Study - Rabow, Jerome; Payne, Keisha E. (European Scientific Journal, ESJ, 2016)
This paper briefly reviews the literature of incivility in the university. We then describe a case study of incivility in a university classroom. We analyze how incivility can be handled as a teaching moment that facilitates deeper learning. Rather than seeing incivility as the disruption of learning, we argue that it provides the possibilities for engagement in a form of pedagogy that stresses inclusiveness and democratic values.